An extensible frame structure for time division multiple access medium access control in vehicular ad‐hoc networks. Issue 12 (21st March 2020) - Sun, Yuanxin; Zhang, Ziheng; Li, Xiaoping; Xiao, Sa; Tang, Wanbin
Abstract: Motivated by the near collision‐free broadcasting performance of time division multiple access vehicular ad‐hoc network medium access control, we propose an extensible frame structure to adapt the varying vehicle traffic density. The scheme aims to provide high reliable and low latency performance. Additionally, the proposed scheme fully considers the nonideal transmission environment, with some mechanisms making the protocol work properly with physical layer errors. We provide the complete specification of the protocol in order to implement the protocol through hardware or software. Then, an algorithm is designed to attain the low latency and high reliable performance. The algorithm assesses the transmission latency based on the current condition, and adjusts the frame length based on the assessment. Finally, a system‐level simulation platform is implemented to verify our proposed scheme. The simulation platform considers a Manhattan grid scenario. Besides, the channel fading, modulation and coding schemes, and user mobilities are considered in the simulation platform. The simulation results show the cost and the advantages of our proposed scheme. Abstract : In this article, we propose an exitensible frame structure to adapt the varying vehicle traffic density. The scheme aims to provide high reliable and low latency performance. Additional, with the help of the supplementary mechanisms, the protocol works properly under the non‐ideal transmission environment.